Air electrode
Patent Information
- Application Number
- JP2023132624
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-28
AI Technical Summary
【0015】 本発明の空気極を含んで構成される金属空気電池は、長期間放電を行うことができる。
Smart Images

Figure 2025027650000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an air electrode, and more particularly to an air electrode used to form a metal-air battery, and a metal-air battery including the air electrode. [Background technology]
[0002] In recent years, the importance of batteries has rapidly increased in many industries, from small portable devices to large applications such as automobiles, and various new battery systems that have advantages mainly in terms of capacity, energy density, and rechargeable battery properties have been developed and improved.
[0003] Batteries including an air electrode, such as metal-air batteries, use a metal material as the negative electrode active material and oxygen in the air as the positive electrode active material. Therefore, there is no need for a space to fill the positive electrode active material, and the negative electrode active material can be filled in that space, realizing a high energy density. For example, air-zinc primary batteries are the batteries with the highest energy density among the batteries in practical use. Various studies have been conducted on such metal-air batteries (for example, see Patent Documents 1 to 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-119289 A [Patent Document 2] JP 2017-174770 A [Patent Document 3] JP 2017-182996 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the discharge reaction (oxygen reduction reaction, ORR) at the air electrode, oxygen in the air reacts with water in the electrolyte on the surface (reaction interface) of the oxygen reduction catalyst contained in the air electrode, as shown in the following formula. O 2 +2H 2 O+4e - →4OH -
[0006] The discharge reaction at the air electrode requires that the three phases of gas (oxygen), liquid (water), and solid (oxygen reduction catalyst at the air electrode) coexist. As described in Patent Document 3, conventional air electrodes use a carbon material as a catalyst or a fluorine-based binder to exhibit water repellency, which can prevent the air electrode from being covered with the electrolyte and sinking to some extent. However, over time, the water repellency is lost and the electrolyte covers the air electrode, resulting in an insufficient supply of oxygen to the reaction interface, causing problems with the discharge reaction. There was room for improvement in order to carry out the discharge reaction over a long period of time.
[0007] The present invention has been made in consideration of the above-mentioned current situation, and has an object to provide a method capable of carrying out a discharge reaction for a long period of time. [Means for solving the problem]
[0008] The present inventors have investigated various methods for enabling a discharge reaction to occur over a long period of time in a metal-air battery, and have focused on the structure of the air electrode. 2 / hour or more, 0.2mg / mm 2 / hour or less, and a catalyst layer containing an oxygen reduction catalyst and a binder, the inventors have discovered that oxygen and water can be supplied to the reaction interface of the air electrode for a long period of time, enabling the discharge reaction to be carried out for a long period of time. They have thus come up with the idea of successfully solving the above-mentioned problems and have arrived at the present invention.
[0009] That is, the present invention (1) has a water permeability rate of 0.01 mg / mm 2 / hour or more, 0.2mg / mm 2 / hour or less, and a catalyst layer containing an oxygen reduction catalyst and a binder. Permeability test: (1) Cut the water-permeability adjusting membrane and nonwoven fabric (thickness 160 μm) into a circle with a diameter of 18 mm. (2) The weight of the cut nonwoven fabric is measured and m 1 (g). (3) The cut-out water permeability adjusting membrane is placed at the bottom of a cylindrical cell with an inner diameter of 16 mm, and then the cut-out nonwoven fabric is placed thereon. (4) 3 g of 6.7MKOH aqueous solution is gently poured into the top of the cylindrical cell. (5) The cylindrical cell is left at 25°C and normal pressure for 1 hour. (6) The weight of the nonwoven fabric is measured again. 2 (g). (7) The water permeability rate K (mg / mm 2 / hour) M=m 2 -m 1 (I) K = M / (8 * 8 * 3.14) x 1000 (II)
[0010] The present invention (2) is the air electrode of the present invention (1), wherein the water permeability adjusting membrane has an ionic conductivity at 25° C. of 20 mS / cm or more.
[0011] The present invention (3) is the air electrode according to the present invention (1) or (2), characterized in that the oxygen reduction catalyst contains a carbon material.
[0012] The present invention (4) is the air electrode according to any one of the present inventions (1) to (3), wherein the laminate structure further comprises a water-repellent film having air permeability on the side of the catalyst layer opposite to the water-permeability adjusting film side.
[0013] The present invention (5) is a metal-air battery comprising the air electrode and the negative electrode of any one of the present inventions (1) to (4), and an electrolytic solution.
[0014] The present invention (6) is the metal-air battery of the present invention (5), in which the negative electrode is a zinc negative electrode. Effect of the Invention
[0015] A metal-air battery comprising the air electrode of the present invention can perform discharge for a long period of time. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a diagram showing one preferred configuration of an air electrode of the present invention. [Diagram 2] FIG. 1 shows an embodiment of a water permeability test. [Diagram 3] 1 is a graph showing discharge voltage (V) versus discharge time (hours) in Examples 1 and 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below. In addition, a combination of two or more of the individual preferred embodiments of the present invention described below is also a preferred embodiment of the present invention.
[0018] <Air electrode> The air electrode of the present invention has a water permeability rate of 0.01 mg / mm 2 / hour or more, 0.2mg / mm 2 / hour or less, and a catalyst layer containing an oxygen reduction catalyst and a binder. As a result, when the battery is in use, the air electrode is kept appropriately wet, and oxygen and water can be supplied sufficiently to the reaction interface of the air electrode for a long period of time.
[0019] (Water permeability adjustment membrane) The water permeability control membrane is a member that is disposed between the catalytic layer of the air electrode and the electrolyte of the battery to control the amount of water supplied from the electrolyte to the catalytic layer. The water permeability control membrane is usually the outermost layer of the air electrode (laminate structure of the air electrode) that can directly contact the electrolyte. If the water permeability control membrane has a water permeability rate of 0.01 mg / mm2 / hour or more, water can be sufficiently supplied to the reaction interface. 2 By keeping the time period within 1 / hour or less, the air electrode can be sufficiently prevented from being covered with the electrolyte, and oxygen can be sufficiently supplied to the reaction interface.
[0020] The water permeability adjusting membrane has a water permeability rate of 0.015 mg / mm 2 / hour or more. The water permeation rate is preferably 0.1 mg / mm 2 / hour or less, and 0.07 mg / mm 2 / hour or less, and more preferably 0.05 mg / mm 2 It is more preferable that the time is 1 / hour or less. The water permeability rate can be appropriately adjusted by adjusting the hydrophilicity of the material of the water permeability adjusting membrane, adjusting the porosity and film thickness of the water permeability adjusting membrane, or making the water permeability adjusting membrane a suitably dense membrane containing an organic binder (organic binder) and inorganic particles as described below.
[0021] The water permeability adjusting membrane has a water permeability rate of 0.01 mg / mm 2 / hour or more, 0.2mg / mm 2 / hour or less, examples of the permeability adjusting membrane include nonwoven fabrics, woven fabrics, and microporous films made of resin materials such as polyethylene, polypropylene, ethylene-propylene copolymer, and cyclic polyolefin polymers; polyvinyl alcohol polymers such as vinylon; aliphatic polyamides; aromatic polyamides; styrene polymers; polyester polymers; and polyphenylene sulfide polymers; and composite membranes containing organic binders and inorganic particles, and may be single-layered or laminated. Among them, the permeability adjusting membrane preferably includes a composite membrane containing an organic binder and inorganic particles. In addition, it is more preferable that the composite membrane is an anion conductive membrane.
[0022] The composite film containing the organic binder and inorganic particles has excellent durability, for example, even in a high oxidation state during charging in a secondary battery, due to its dense structure. In addition, when the composite film is used in a battery using metallic zinc and / or a zinc compound as the negative electrode active material, which is prone to morphological changes accompanying charging and discharging, the substantial amount of electrolyte in the composite film is limited, and the concentration of ions (e.g., zincate ions) derived from the free active material in the composite film is low, so that the generation and growth of dendrites occurring during the dissolution and deposition reaction of the active material component (e.g., zinc component) can be suppressed, and the battery life can be extended. In addition, the composite film contains inorganic particles, so that the inorganic particle surface becomes an ion conduction path, and the organic binder can be sufficiently prevented from filling most of the gaps between the particles when binding the particles, and the ion conductivity of the composite film can be sufficiently high. By making the ion conductivity inside the battery sufficiently high and making it a storage battery with low internal resistance, the battery can be operated appropriately, contributing to a long life.
[0023] [Organic binder] The organic binder is a binder capable of binding and fixing inorganic particles. The organic binder is preferably an organic polymer (binder polymer). The binder polymer may be a homopolymer or a copolymer, except when clearly limited.
[0024] The binder polymer may be either thermoplastic or thermosetting, but is preferably a component having a glass transition temperature of less than 60° C. The binder polymer binds the particles together, thereby contributing to the structural stability of the water permeability control film. The binder polymer preferably has a glass transition temperature of 50° C. or less. In this specification, the glass transition temperature is measured by applying a material such as a polymer to a glass plate, drying the dried material at 120°C for 1 hour, and using a differential scanning calorimeter (apparatus name: thermal analyzer DSC3100S, BRVKER) at a heating rate of 10°C / min.
[0025] The binder polymer is preferably a non-crystalline binder polymer, which is easily bonded to surrounding members and functions favorably as a binding component. Examples of the binder polymer include polymers containing a hydrocarbon moiety such as polyethylene or polypropylene; aromatic group-containing polymers such as polystyrene; ether group-containing polymers such as alkylene glycol; halogen atom-containing polymers such as polytetrafluoroethylene; epoxy resins; polymers containing quaternary ammonium salts or quaternary phosphonium salts; ion exchange polymers used in cation-anion exchange membranes; conjugated diene polymers; (meth)acrylic polymers; amino group-containing polymers such as polyethyleneimine; carbamate group-containing polymers; carbamide group-containing polymers; epoxy group-containing polymers; heterocyclic and / or ionized heterocyclic moiety-containing polymers; polymer alloys; and heteroatom-containing polymers. One or more of these can be used. Among these, the binder polymer is preferably a halogen-containing polymer or a conjugated diene polymer, and more preferably a halogen-containing polymer from the viewpoint of further improving the life of the secondary battery by maintaining a particulate shape and filling the voids in the film to densify the film. These polymers act as binders for the inorganic particles contained in the water-permeability adjusting membrane, and can prevent the occurrence of cracks.
[0026] Preferred examples of the halogen-containing polymer include polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, and polypentafluoroethylene, and among these, polytetrafluoroethylene, polyvinylidene fluoride, and polypentafluoroethylene are more preferred.
[0027] The conjugated diene polymer has monomer units derived from a conjugated diene monomer. The conjugated diene polymer may be one or more of styrene-butadiene polymers (SBR), carboxy-modified styrene-butadiene polymers, polybutadiene polymers, carboxy-modified polybutadiene polymers, polyisoprene polymers, carboxy-modified polyisoprene polymers, acrylonitrile-butadiene polymers, carboxy-modified acrylonitrile-butadiene polymers, etc. Among these, styrene-butadiene polymers and carboxy-modified styrene-butadiene polymers are preferred.
[0028] The conjugated diene polymer may have monomer units derived from other unsaturated monomers other than monomer units derived from aliphatic conjugated diene monomers, monomer units derived from aromatic vinyl monomers, and monomer units derived from unsaturated monomers having a carboxy group and / or a carboxylate group which is a salt thereof. In 100% by mass of the above conjugated diene-based polymer, the mass proportion of monomer units derived from other unsaturated monomers is preferably 30% by mass or less, more preferably 5% by mass or less, and even more preferably 0.1% by mass or less.
[0029] The (meth)acrylic polymer has monomer units derived from monomers having a (meth)acryloyl group other than (meth)acrylic acid monomers, and a representative example is one mainly composed of monomer units derived from (meth)acrylic acid ester monomers.
[0030] "Containing mainly monomer units derived from (meth)acrylic acid ester monomers" means that the content of monomer units derived from (meth)acrylic acid ester monomers in 100% by mass of the (meth)acrylic polymer is 50% by mass or more. Specific examples of the (meth)acrylic acid ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, and decyl (meth)acrylate.
[0031] The (meth)acrylic polymer may contain, in addition to monomer units derived from (meth)acrylic acid ester monomers, monomer units derived from unsaturated monomers having a carboxy group and / or a carboxylate group, which is a salt thereof, and monomer units derived from other unsaturated monomers. In 100% by mass of the (meth)acrylic polymer, the mass proportion of monomer units derived from other unsaturated monomers is preferably 30% by mass or less, more preferably 5% by mass or less, and even more preferably 0.1% by mass or less.
[0032] The weight average molecular weight of the binder polymer is preferably 200 to 7,000,000. The weight average molecular weight is more preferably 400 to 6,500,000, and further preferably 500 to 5,000,000. The weight average molecular weight can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent weight average molecular weight. Equipment: Tosoh Corporation HCL-8220GPC Column: TSKgel Super AWM-H Eluent (LiBr H 2 O, NMP containing phosphoric acid): 0.01 mol / L
[0033] The strength, ionic conductivity (anionic conductivity), etc. of the binder polymer can be suitably adjusted by applying heat, pressure, etc.
[0034] The mass ratio of the organic binder (preferably a binder polymer) is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and particularly preferably 20% by mass or more, based on 100% by mass of the water permeability control membrane. The mass ratio is preferably 70% by mass or less, more preferably 60% by mass or less, even more preferably 50% by mass or less, even more preferably 45% by mass or less, and particularly preferably 40% by mass or less.
[0035] [Inorganic particles] In the present specification, the inorganic particles are generally inorganic compound particles that do not have a glass transition temperature. The inorganic particles may be, for example, particles entirely composed of an inorganic compound, or particles whose surfaces are coated with an inorganic compound.
[0036] In the following, particles entirely composed of an inorganic compound will be described, but the same can be said about the inorganic compound portion of particles whose surfaces are coated with an inorganic compound. As the inorganic compound constituting the inorganic particles, various inorganic compounds can be used, but for example, at least one selected from the group consisting of oxides, hydroxides, layered double hydroxides, and phosphate compounds is preferable. In this specification, hydroxide refers to a compound having a hydroxy group other than layered double hydroxides.
[0037] Examples of the oxide include lithium oxide, sodium oxide, potassium oxide, magnesium oxide, calcium oxide, barium oxide, scandium oxide, yttrium oxide, lanthanoid oxide, titanium oxide, zirconium oxide, niobium oxide, ruthenium oxide, nickel oxide, palladium oxide, copper oxide, cadmium oxide, boron oxide, aluminum oxide, gallium oxide, indium oxide, thallium oxide, silicon oxide, germanium oxide, tin oxide, lead oxide, phosphorus oxide, and bismuth oxide. One or more of these oxides can be used. Among them, oxides that are stable in the dispersion liquid during film formation or in a storage battery under alkaline conditions are preferred, and examples of the oxides include magnesium oxide, calcium oxide, titanium oxide, zirconium oxide, and aluminum oxide, and magnesium oxide, titanium oxide, and zirconium oxide are more preferred. Note that zirconium oxide may be a solid solution of elements such as yttrium, scandium, and ytterbium, or may have oxygen defects.
[0038] Examples of the hydroxide include lithium hydroxide, sodium hydroxide, potassium hydroxide, magnesium hydroxide, calcium hydroxide, barium hydroxide, scandium hydroxide, yttrium hydroxide, lanthanoid hydroxide, titanium hydroxide, zirconium hydroxide, niobium hydroxide, ruthenium hydroxide, nickel hydroxide, palladium hydroxide, copper hydroxide, cadmium hydroxide, boric acid, aluminum hydroxide, gallium hydroxide, indium hydroxide, thallium hydroxide, silicic acid, germanium hydroxide, tin hydroxide, lead hydroxide, phosphoric acid, bismuth hydroxide, etc., and one or more of these can be used. Among them, those with low solubility under alkaline conditions are preferred, such as magnesium hydroxide, calcium hydroxide, titanium hydroxide, and zirconium hydroxide, and magnesium hydroxide is more preferred.
[0039] The layered double hydroxide has the following general formula: [M 1 1-x M 2 x (OH) 2 ](A n- ) x / nmH 2 O (M 1 represents a divalent metal ion selected from Mg, Fe, Zn, Ca, Li, Ni, Co, Cu, and Mn. 2 represents a trivalent metal ion selected from Al, Fe, Mn, Co, Cr, and In. n- is Cl - , NO 3 - , CO 3 2- , COO - These represent anions with a valence of 1 or more and 3 or less. Among them, A n- It is preferable that represents a divalent or lower anion. m is a number of 0 or more, n is a number of 1 or more and 3 or less, and x is a number of 0.20 or more and 0.40 or less.) is a compound represented by the above-mentioned, and examples of such layered double hydroxides include hydrotalcite, manasseite, motsukoreite, stichtite, schoglenite, barbartonite, pyraurite, iomite, chloromagalminite, hydrocalumite, greenlast 1, berthierine, takovite, liebesite, honnesite, yeardolite, meixenerite, etc., and one or more of these can be used. Among them, M in the above general formula is preferred because of its ease of industrial use. 1 Mg, M 2 Hydrotalcite in which is Al is preferred. These layered double hydroxides may be, for example, compounds obtained by dehydrating the compound through firing at 150°C or higher and 900°C or lower, compounds in which the anions between the layers have been decomposed, or compounds in which the anions between the layers have been exchanged for hydroxide ions or the like. The layered double hydroxide may have a compound having a functional group such as a hydroxyl group, an amino group, a carboxyl group, a silanol group, etc. The layered double hydroxide may have an organic substance between the layers.
[0040] The above-mentioned phosphate compound is, for example, hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2), magnesium hydroxyapatite in which some or all of the calcium ions of hydroxyapatite are replaced with magnesium, strontium hydroxyapatite in which calcium ions are replaced with strontium, barium hydroxyapatite in which calcium ions are replaced with barium, etc. Among these, hydroxyapatite and magnesium hydroxyapatite are preferred.
[0041] Among them, the inorganic compound is preferably a magnesium-containing compound. The inorganic compound is preferably a hydroxide, a layered double hydroxide, or a phosphate compound, and more preferably a layered double hydroxide and / or a hydroxide. From the viewpoint of improving the strength of the membrane, the inorganic compound is more preferably a hydroxide, from the viewpoint of improving the ion conductivity of the membrane, it is more preferably a layered double hydroxide or magnesium hydroxide, and from the viewpoint of improving the durability of the membrane, it is particularly preferably magnesium hydroxide.
[0042] The shape of the inorganic particles may be fine powder, powder, granules, granules, scales, polyhedrons, rods, curved surfaces, or the like. The inorganic particles preferably have an average particle size of 2 μm or less. The average particle size is more preferably 1 μm or less, and even more preferably 0.5 μm or less. The average particle size is preferably 1 nm or more, more preferably 10 nm or more, and even more preferably 100 nm or more. In this specification, the average particle size refers to the average particle size in a volume-based particle size distribution obtained by particle size distribution measurement using a dynamic light scattering method. In the measurement, the active material particles are diluted with a dispersion medium (ion-exchanged water containing 0.2% sodium hexametaphosphate) to prepare a measurement sample. As a particle size distribution measuring device using the dynamic light scattering method, for example, a concentrated particle size analyzer FPAR-1000AS manufactured by Otsuka Electronics Co., Ltd. can be used.
[0043] Particles having a volume average particle size in the above range can be produced, for example, by a method of pulverizing particles using a ball mill or the like, dispersing the resulting coarse particles in a dispersant to obtain a desired particle size, and then drying and solidifying the particles, or by a method of screening the coarse particles through a sieve or the like to select the particle size, or by a method of optimizing preparation conditions in the particle production stage to obtain (nano)particles having a desired particle size.
[0044] The inorganic particles may have an aspect ratio (length / width) of at least 1. The aspect ratio (length / width) is preferably at most 8. The aspect ratio (length / width) is more preferably at most 5, even more preferably at most 2, and particularly preferably at most 1.5. The aspect ratio (length / width) is calculated as described above. The aspect ratio (length / width) can be determined from the shape of the particle observed by SEM.
[0045] The mass proportion of the inorganic particles is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more, based on 100% by mass of the water permeability adjusting membrane. The upper limit of the mass proportion of the inorganic particles is not particularly limited, but is preferably 95 mass % or less, and more preferably 90 mass % or less, relative to 100 mass % of the water permeability adjusting membrane.
[0046] In the water permeability adjusting membrane, the mass ratio of the organic binder to the inorganic particles is preferably 10 / 1 to 1 / 100, more preferably 8 / 1 to 1 / 80, even more preferably 5 / 1 to 1 / 30, still more preferably 3 / 1 to 1 / 20, still more preferably 2 / 1 to 1 / 15, and particularly preferably 1 / 1 to 1 / 10.
[0047] In the water permeability adjusting membrane, the volume ratio of the organic binder to the inorganic particles is preferably 5 / 1 to 1 / 200. More preferably, it is 4 / 1 to 1 / 160, and even more preferably, it is 5 / 2 to 1 / 60. Still more preferably, it is 2 / 1 to 1 / 40. Still more preferably, it is 3 / 2 to 1 / 20. Especially preferably, it is 1 / 1 to 1 / 10.
[0048] [Porous support] The water permeability adjusting membrane may further have a porous support (porous substrate) made of a polyolefin-based polymer or the like, and may be a resin-impregnated layer in which the porous support is impregnated with a mixture (dispersion) of an organic binder, inorganic particles, and, if necessary, other components, or may have a laminate structure obtained by contacting the mixture with the porous substrate and drying the mixture if necessary.
[0049] The porous support is not particularly limited, but suitable examples include nonwoven fabrics, woven fabrics, and microporous films made of resin materials such as polyolefin-based polymers such as polyethylene, polypropylene, ethylene-propylene copolymers, and cyclic polyolefin-based polymers; polyvinyl alcohol-based polymers such as vinylon; aliphatic polyamides; aromatic polyamides; styrene-based polymers; polyester-based polymers; polysulfone-based polymers such as polysulfone, polyethersulfone, and polyphenylsulfone; and polyphenylene sulfide-based polymers. Among these, polyolefin-based polymers and polyvinyl alcohol-based polymers are more preferable. The water-permeability adjusting membrane may be a membrane in which a resin-impregnated layer obtained by impregnating a porous support with the mixture is at least partially integrated with the porous support, in which the solid content of the mixture fills at least a portion of the pores in the porous support.
[0050] When the water permeability adjusting membrane further has a porous support, the mass ratio of the porous support is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on 100% by mass of the water permeability adjusting membrane. The mass ratio is preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less.
[0051] The density of the porous support is 0.05 g / cm from the viewpoint of impregnation with the mixture. 3 More than 0.1 g / cm is preferable. 3 More preferably, the density is 2.0 g / cm or more. 3 Less than 1.0 g / cm is preferred. 3 The following is even more preferred:
[0052] The membrane thickness of the porous support is preferably 300 μm or less, more preferably 200 μm or less, from the viewpoints of improving the metal-air battery performance and the water permeability adjusting membrane strength, and suppressing separation from the inorganic component during impregnation, and is preferably 5 μm or more, more preferably 20 μm or more.
[0053] [Other ingredients] The water permeability adjusting film may contain other components in addition to the organic binder and inorganic particles.
[0054] The water permeability adjusting membrane may contain a water-soluble polymer as a dispersant for inorganic particles or the like. Examples of the water-soluble polymer include celluloses such as carboxymethyl cellulose; poly(meth)acrylic acids (salts) such as sodium polyacrylate; and copolymers of (meth)acrylic acid (salts) and unsaturated carboxylic acids (salts) such as maleic acid (salts) or unsaturated sulfonic acids (salts) such as vinyl sulfonic acid (salts). One or more of these may be used.
[0055] When the water-permeability adjusting film contains a water-soluble polymer, the content of the water-soluble polymer is preferably 0.1% by mass or more in 100% by mass of the water-permeability adjusting film in order to fully disperse the inorganic particles and exert its effect. Also, the content is preferably 3% by mass or less in order to further suppress the water-soluble polymer from absorbing an electrolyte such as water and plasticizing the water-permeability adjusting film.
[0056] The water permeability adjusting film may further contain other inorganic components such as conductive carbon and conductive ceramics. The content of other inorganic components in the water-permeability adjusting membrane is preferably 0.1% by mass or more and 10% by mass or less, based on 100% by mass of the water-permeability adjusting membrane.
[0057] The water permeability adjusting membrane preferably has an ionic conductivity of 20 mS / cm or more at 25° C. The ionic conductivity is more preferably 25 mS / cm or more. The upper limit of the ionic conductivity is not particularly limited, but is usually 1000 mS / cm or less. In this specification, the ionic conductivity is measured by the method described in the Examples.
[0058] The ionic conductivity can be appropriately adjusted by adjusting the porosity and thickness of the water-permeability adjusting membrane, by making the water-permeability adjusting membrane a composite membrane containing an organic binder and inorganic particles, by adjusting the conditions such as temperature and pressure during membrane formation, or by adjusting the mass ratio of the inorganic particles.
[0059] The average thickness of the water permeability adjusting membrane is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more. This can sufficiently prevent the occurrence of breakage during membrane formation. The average thickness of the water permeability adjusting membrane is, for example, preferably 1000 μm or less, more preferably 500 μm or less, and even more preferably 200 μm or less. This is advantageous in terms of cost and also provides sufficiently excellent ion permeability. The average thickness of the water permeability adjusting membrane is the average value of measurements taken at random ten points using a micrometer.
[0060] The method for producing the water permeability adjusting membrane is not particularly limited. For example, the water permeability adjusting membrane can be produced by preparing a composition (also referred to simply as the composition according to the present invention in this specification) used for forming the water permeability adjusting membrane, and forming the composition into a membrane. First, the raw materials of the composition according to the present invention (for example, inorganic particles, an organic binder, and other components such as a dispersant for the inorganic particles, if necessary) are mixed. For mixing, a mixer, a blender, a kneader, a sand mill, a bead mill, a ready mill, a roll mill, a ball mill, or the like can be used. When mixing, water, an organic solvent such as methanol, ethanol, propanol, isopropanol, butanol, hexanol, tetrahydrofuran, or N-methylpyrrolidone, or a mixed solvent of water and an organic solvent may be added as a medium. After mixing, filtration, degassing, etc. can be carried out as necessary to obtain the composition according to the present invention.
[0061] The method for producing a water permeability control film from the composition according to the present invention is not particularly limited, and may be a method (casting method) in which the composition according to the present invention is coated on a release substrate such as a mirror-finished metal roll or a polyethylene terephthalate (PET) film, dried, and the obtained coating film is peeled off to obtain a film, a method of rolling with a roll to form a film, a method of rolling with a flat plate press or the like to form a film, a method of forming a film such as an injection molding method or an extrusion molding method, or a method of coating on an electrode sheet (a sheet corresponding to a catalyst layer), drying, and forming a film integrated with the electrode sheet. These forming methods may be used alone or in combination of two or more methods.
[0062] During and / or after the step of forming the composition according to the present invention into a film, the film is preferably dried. The film may be dried after it has been formed by heating it as necessary. The heating temperature and heating time of the film may be appropriately set.
[0063] When a metal-air battery is constructed using the air electrode of the present invention, the water permeability adjusting membrane is disposed on the electrolyte side of the metal-air battery, and is disposed between the catalyst layer of the air electrode and the electrolyte of the metal-air battery.
[0064] (catalyst layer) The catalyst layer includes an oxygen reduction catalyst and a binder. The catalyst layer is also called an oxygen reduction layer because it exerts an action of reducing oxygen. The catalyst layer may be the outermost layer of the air electrode (a laminated structure of the air electrode) or may be an inner layer between the outermost layers of the air electrode.
[0065] [Oxygen reduction catalyst] The oxygen reduction catalyst at least functions as an oxygen reduction catalyst, and may further function as an oxygen generation catalyst. As the oxygen reduction catalyst, for example, a carbon material, a metal element, a metal alloy, or a metal compound can be suitably used, and among them, a carbon material is preferable. If the oxygen reduction catalyst is hydrophobic in this way, it can be more prevented from being completely covered with water, and the discharge reaction can be carried out for a longer period of time. As the carbon material, conductive carbon such as Ketjen Black, acetylene black, denka black, carbon nanotube, fullerene, etc. are more preferable, and one or more of these can be used.
[0066] When the oxygen reduction catalyst is a simple metal, a metal alloy, or a metal compound, the metal species that can be used may be a metal, metal oxide, or metal complex made of platinum, palladium, iridium, rhodium, ruthenium, gold, silver, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, or the like, or a composite of an alloy, metal oxide, or metal complex made of a combination of two or more types of metals.
[0067] When the oxygen reduction catalyst is a metal compound, for example, one or more of perovskite-type transition metal oxides, pyrochlore-type oxides, spinel-type oxides, rutile-type compounds, layered rock salt-type compounds having a layered crystal structure, delafossite-type compounds, and brownmillerite-type compounds can be used.
[0068] The perovskite transition metal oxide may be, for example, a compound represented by the formula ABO 3 A represents a transition metal element or an alkaline earth metal element, and B represents a transition metal element. Examples of the perovskite-type transition metal oxide include LaCoO 3 and those in which a portion of La is replaced with Ca, Sr, Ba, etc., and those in which a portion of Co is replaced with Mn, Ni, Cu, Fe, Ir, etc.
[0069] The pyrochlore oxide is, for example, a compound represented by the formula A 2 B 2 O 7 A and B are the same or different and each represents a transition metal element or a rare earth element. Examples of the pyrochlore oxide include Pb 2 Ru 2 O 6.5 , Bi 2 Ru 2 O 7 and those in which part of the Ru is replaced with Ir or Pb.
[0070] The spinel oxide may be, for example, a compound represented by the formula AB 2 O 4 A represents a transition metal element, Li, or Mg. B represents a transition metal element. The spinel oxide is, for example, LiMn 2 O 4 , in which a part of the Mn is replaced with Co or Fe; Co 3 O 4 , in which part of the Co is replaced by Ni, Cu, Mn, etc.
[0071] The rutile compound is, for example, of the formula AB 2 A represents a transition metal element, Sn, or Ge. B represents oxygen or a halogen element, and is preferably oxygen. For example, the rutile compound is preferably a rutile oxide. Examples of rutile oxides include IrO 2 , RuO 2 Examples include:
[0072] The layered rock-salt compound has a layered crystal structure in which, for example, an alkali metal element and a transition metal element are alternately arranged, and is preferably a layered rock-salt oxide. Examples of the layered rock-salt oxide include LiCoO 2 , Na 0.08 Ni 0.9 Fe 0.1 O 2 Examples include:
[0073] The delafossite type compound is, for example, represented by the formula ABO 2 A represents a transition metal element, and is preferably a copper element. B represents a trivalent metal element. The delafossite oxide is, for example, CuRhO 2 Examples include:
[0074] The Brownmillerite type compound is, for example, represented by the formula A 2 B 2 O 5 A is preferably a Brownmillerite-type oxide represented by the formula: A is the same or different and represents an alkaline earth metal element, and is preferably a calcium element. B is the same or different and represents a transition metal element. The Brownmillerite-type oxide is, for example, Ca 2 FeCoO 5 Examples include:
[0075] The mass ratio of the oxygen reduction catalyst contained in the catalyst layer is preferably 5% by mass or more, based on 100% by mass of the entire catalyst layer. When the ratio of the oxygen reduction catalyst is in this range, the air electrode can have a sufficient function. It is more preferably 10% by mass or more, even more preferably 30% by mass or more, even more preferably 50% by mass or more, even more preferably 60% by mass or more, even more preferably 70% by mass or more, and particularly preferably 80% by mass or more. In addition, the mass ratio is preferably 99% by mass or less, more preferably 98% by mass or less, even more preferably 97% by mass or less, and particularly preferably 95% by mass or less.
[0076] [Binding Agent] As the binder, various materials can be used, but an organic binder is preferable, and an organic polymer (binder polymer) is more preferable. As the binder polymer, the binder polymer used in the water permeability adjusting membrane described above can be suitably used. The mass proportion of the binder in the catalyst layer is preferably 1 to 50 mass %, more preferably 2 to 40 mass %, further preferably 3 to 30 mass %, and particularly preferably 5 to 20 mass %.
[0077] The catalyst layer may further contain a conductive assistant. Examples of the conductive assistant that can be used include conductive ceramics, zinc, zinc powder, zinc alloy, zinc used in (alkaline) (storage) dry batteries and air batteries (hereinafter collectively referred to as metallic zinc), metals such as copper, brass, nickel, silver, bismuth, indium, lead, tin, etc., and carbon materials such as acetylene black, carbon black, carbon nanotubes, carbon nanofibers, graphene, etc. Among the conductive assistants, those that also function as oxygen reduction catalysts are considered to be oxygen reduction catalysts rather than conductive assistants in calculating the content ratio in the catalyst layer.
[0078] When the catalyst layer further contains a conductive assistant, the content of the conductive assistant in the catalyst layer can be 0.0001 to 90% by mass, preferably 0.0005 to 85% by mass, and more preferably 0.001 to 80% by mass.
[0079] The catalyst layer may further contain, as other components, at least one selected from the group consisting of inorganic compounds, organic compounds, and organic compound salts. In the catalyst layer, the mass proportion of other components is preferably 10 mass % or less, more preferably 1 mass % or less, and even more preferably 0.1 mass % or less.
[0080] The average thickness of the catalyst layer is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. The average thickness of the catalyst layer is, for example, preferably 1000 μm or less, and more preferably 500 μm or less. The average thickness of the catalyst layer is an average value measured at random ten points using a micrometer. When the air electrode of the present invention has two or more catalyst layers, for example, when the catalyst layers are formed on both sides of a layered current collector, the average thickness of the catalyst layers is the sum of the average thicknesses of the catalyst layers. When the air electrode of the present invention has two or more catalyst layers, the two or more catalyst layers are usually disposed on one side of the water permeability control membrane.
[0081] In one preferred embodiment of the present invention, the air electrode (laminate structure in the air electrode) further comprises a water-repellent film having air permeability on the side opposite to the water permeability control film side of the catalyst layer. When the air electrode further comprises the water-repellent film, the water-repellent film is usually the outermost layer of the air electrode (laminate structure in the air electrode). When the air electrode of the present invention further includes the water-repellent film, the air electrode can be more sufficiently prevented from being covered with the electrolyte, and the amount of the electrolyte can be effectively prevented from decreasing due to leakage or volatilization of the electrolyte from the air electrode. The water-repellent film has air permeability if its air permeability is 10,000 seconds or less in Gurley value, and preferably 9,500 seconds or less. The Gurley value is preferably 500 seconds or more, and more preferably 1000 seconds or more. The Gurley value was measured using a Gurley meter in accordance with JIS P 8117 to measure the time it takes for 100 cc of air to pass through. The Gurley value is an index that indicates the ease with which gas can pass through, and the higher the value, the more difficult it is for gas to pass through.
[0082] The water-repellent film may be one of the following: a polyolefin nonwoven fabric such as polyethylene or polypropylene; a water-repellent film formed from a fluorine-containing polymer such as a polymer containing a polytetrafluoroethylene moiety or a polymer containing a polyvinylidene fluoride moiety; a water-repellent porous film such as Celgard 2501 or TEMISH (registered trademark) (Nitto Denko Corporation, http: / / www.nitto.com / jp / ja / products / group / temish / about / ); or two or more of these may be laminated together. The water-repellent film is disposed on the atmospheric side when a metal-air battery is constructed using the air electrode.
[0083] The water-repellent film has an average thickness of preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. The water-repellent film has an average thickness of, for example, preferably 1000 μm or less, and more preferably 500 μm or less. The average thickness of the water-repellent film is the average value of measurements taken at random ten points using a micrometer.
[0084] In one preferred embodiment of the present invention, the air electrode of the present invention does not include the water-repellent film. This allows costs to be reduced. Furthermore, the air electrode of the present invention is capable of a long-term discharge reaction even if it does not include the water-repellent film.
[0085] The air electrode may further include a current collector. The current collector is preferably disposed so as to be in contact with the catalyst layer. For example, the current collector preferably constitutes at least one layer of the laminated structure of the air electrode, and the catalyst layer is preferably disposed so as to be in contact with one or both sides of the current collector layer. The material of the current collector is not particularly limited, and examples thereof include (electrolytic) copper foil, copper mesh (expanded metal), foamed copper, punched copper, copper alloys such as brass, brass foil, brass mesh (expanded metal), foamed brass, punched brass, nickel foil, corrosion-resistant nickel, nickel mesh (expanded metal), punched nickel, metallic zinc, corrosion-resistant metallic zinc, zinc foil, zinc mesh (expanded metal), (punched) steel plate, nonwoven fabrics imparted with electrical conductivity; (electrolytic) copper foil, copper mesh (expanded metal), foamed copper, punched copper, copper alloys such as brass, brass foil, brass mesh (expanded metal), foamed brass, punched brass, nickel foil, corrosion-resistant nickel, nickel metal (Expanded metal) · Perforated nickel · Metal zinc · Corrosion-resistant metal zinc · Zinc foil · Zinc mesh (Expanded metal) · (Perforated) steel plate · Nonwoven fabric; (Electrolytic) copper foil plated with Ni · Zn · Sn · Pb · Hg · Bi · In · Tl · brass, etc. · Copper foil (Expanded metal) · Foamed copper · Perforated copper · Brass and other copper alloys · Brass foil · Brass mesh (Expanded metal) · Foamed brass · Perforated brass · Nickel foil · Corrosion-resistant nickel · Nickel mesh (Expanded metal) · Perforated nickel · Metal zinc · Corrosion-resistant metal zinc · Zinc foil · Zinc mesh (Expanded metal) · (Perforated) steel plate · Nonwoven fabric; Silver; Materials used as current collectors and containers in alkaline (storage) batteries and zinc-air batteries.
[0086] Fig. 1 is a diagram showing one suitable configuration of the air electrode of the present invention. The air electrode 10 has a laminated structure consisting of a water-permeability adjusting membrane 11, a catalyst layer (oxygen reduction layer) 13, and a breathable water-repellent membrane 15. The water-permeability adjusting membrane 11 is disposed on the electrolyte 20 side of the metal-air battery, and the breathable water-repellent membrane 15 is disposed on the atmosphere 30 side.
[0087] <Metal-air battery> The metal-air battery of the present invention comprises the air electrode of the present invention, a negative electrode, and an electrolyte solution.
[0088] The air electrode of the present invention is disposed in a position where it is in contact with the electrolyte and also in contact with oxygen in the air (atmosphere). The water permeability control film of the air electrode is usually disposed on the electrolyte side. When the air electrode further includes a water-repellent film, the water-repellent film is usually disposed on the opposite side to the electrolyte side (atmosphere side).
[0089] (Negative electrode) The negative electrode generally includes a negative electrode active material layer. The negative electrode active material included in the negative electrode active material layer may be any of those generally used as a negative electrode active material for batteries, such as cadmium species, lithium species, sodium species, magnesium species, lead species, zinc species, tin species, silicon-containing materials, hydrogen storage alloy materials, and precious metal materials such as platinum. As the negative electrode active material, among the above, zinc species or cadmium species are preferred, and zinc species are more preferred. In other words, the negative electrode is preferably a zinc negative electrode or a cadmium negative electrode, and more preferably a zinc negative electrode. Here, the zinc species means a simple metal of zinc or a zinc compound, and the cadmium species means a simple metal of cadmium or a cadmium compound. The same applies to lithium species, sodium species, magnesium species, lead species, zinc species, and tin species. Examples of compounds include oxides, sulfides, and hydroxides.
[0090] The negative electrode active material has an average particle size of preferably 1 nm to 500 μm, more preferably 5 nm to 200 μm, further preferably 10 nm to 100 μm, and particularly preferably 10 nm to 60 μm. The average particle size can be measured using a particle size distribution measuring device.
[0091] The negative electrode preferably has a negative electrode active material layer formed so as to contact the current collector. The mass ratio of the negative electrode active material contained in the negative electrode active material layer is preferably 40 mass% or more in 100 mass% of the entire negative electrode active material layer. When the amount of the active material is within such a range, the capacity of the electrode can be made sufficient. More preferably, it is 60 mass% or more, even more preferably, it is 80 mass% or more, and particularly preferably, it is 85 mass% or more. In addition, the mass ratio is preferably 99.9 mass% or less, more preferably, it is 99.5 mass% or less, even more preferably, it is 99 mass% or less, and particularly preferably, it is 98 mass% or less.
[0092] The negative electrode active material layer may contain a binder, a conductive assistant, and the like in addition to the active material. As the binder, the binder polymer used in the water permeability adjusting membrane described above can be suitably used.
[0093] The mass proportion of the binder in the entire active material layer is preferably 0.3 to 30 mass %, more preferably 0.5 to 15 mass %, still more preferably 1 to 10 mass %, and particularly preferably 2 to 6 mass %.
[0094] As the conductive assistant, the conductive assistant used in the catalyst layer described above can be suitably used. When the negative electrode active material layer contains a conductive assistant, the proportion of the conductive assistant is preferably 0.0001 to 100 mass% relative to 100 mass% of the active material in the negative electrode active material layer. When the content of the conductive assistant is within this range, better battery performance can be exhibited. The content is more preferably 0.0005 to 60 mass%, and even more preferably 0.001 to 40 mass%.
[0095] The negative electrode active material layer may contain, as other components, at least one selected from the group consisting of a compound having at least one element selected from the group consisting of elements belonging to Groups 1 to 17 of the periodic table, an organic compound, and an organic compound salt. When the negative electrode active material layer contains other components, the content of the other components in the negative electrode active material layer is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 1% by mass or less.
[0096] The average thickness of the negative electrode active material layer is preferably 100 μm or more, more preferably 200 μm or more, even more preferably 500 μm or more, and particularly preferably 1 mm or more. The average thickness of the negative electrode active material layer is, for example, preferably 10 mm or less, more preferably 5 mm or less. The average thickness of the negative electrode active material layer is an average value measured at random ten points using a micrometer.
[0097] In the present invention, the material of the negative electrode current collector is not particularly limited, and the current collector used in the air electrode described above can be suitably used.
[0098] (electrolyte) The electrolyte constituting the metal-air battery of the present invention can be one that is commonly used as an electrolyte for storage batteries, and is not particularly limited, but an aqueous electrolyte is preferred. Examples of the aqueous electrolyte include potassium hydroxide aqueous solution, sodium hydroxide aqueous solution, lithium hydroxide aqueous solution, zinc sulfate aqueous solution, zinc nitrate aqueous solution, zinc phosphate aqueous solution, zinc acetate aqueous solution, and the like. Among these, alkaline electrolytes such as potassium hydroxide aqueous solution, sodium hydroxide aqueous solution, and lithium hydroxide aqueous solution are preferred. The aqueous electrolyte can be used alone or in combination. The aqueous electrolyte may contain an organic solvent-based electrolyte. Examples of organic solvent-based electrolytes include ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, dimethoxymethane, diethoxymethane, dimethoxyethane, tetrahydrofuran, methyltetrahydrofuran, diethoxyethane, dimethylsulfoxide, sulfolane, acetonitrile, benzonitrile, ionic liquids, fluorine-containing carbonates, fluorine-containing ethers, polyethylene glycols, and fluorine-containing polyethylene glycols, and one or more of these can be used.
[0099] (Separator) The metal-air battery of the present invention preferably includes a separator between the air electrode and the negative electrode. The separator preferably contains inorganic particles and a binder polymer. As the inorganic particles and the binder polymer, the inorganic particles and the binder polymer in the water permeability adjusting membrane described above can be suitably used.
[0100] The mass ratio of the binder polymer is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and particularly preferably 20% by mass or more, based on 100% by mass of the separator. The mass ratio is preferably 70% by mass or less, more preferably 60% by mass or less, even more preferably 50% by mass or less, particularly preferably 45% by mass or less, and particularly preferably 40% by mass or less.
[0101] The mass proportion of the inorganic particles is preferably 50 mass % or more, more preferably 60 mass % or more, and even more preferably 65 mass % or more, based on 100 mass % of the separator. The upper limit of the mass proportion of the inorganic particles is not particularly limited, but is preferably 95 mass % or less, more preferably 90 mass % or less, and even more preferably 85 mass % or less, relative to 100 mass % of the separator.
[0102] The mass ratio of the polymer to the inorganic particles in the separator is preferably 5,000,000 / 1 to 1 / 100,000. More preferably, it is 2,000,000 / 1 to 1 / 50,000, and even more preferably, it is 1,000,000 / 1 to 1 / 10,000. Still more preferably, it is 1,000,000 / 1 to 1 / 100. Still more preferably, it is 100 / 3 to 75 / 100. Especially preferably, it is 100 / 50 to 75 / 100.
[0103] The separator preferably further comprises a porous substrate. The porous substrate is not particularly limited, but suitable examples thereof include nonwoven fabrics, woven fabrics, and microporous films made of resin materials such as polyethylene (PE), polypropylene (PP), ethylene-propylene copolymers, and cyclic polyolefin polymers; polyvinyl alcohol polymers such as vinylon; aliphatic polyamides; aromatic polyamides; styrene polymers; polyester polymers; and polyphenylene sulfide polymers. Among these, polyolefin polymers and polyvinyl alcohol polymers are more preferable.
[0104] The mass ratio of the porous substrate is preferably 1 mass% or more, more preferably 3 mass% or more, and even more preferably 5 mass% or more, based on 100 mass% of the separator. The mass ratio is preferably 50 mass% or less, more preferably 30 mass% or less, even more preferably 20 mass% or less, even more preferably 15 mass% or less, and particularly preferably 10 mass% or less.
[0105] The separator may contain other components in addition to the binder polymer, inorganic particles, and porous substrate. For example, the separator may contain a water-soluble polymer as a dispersant for inorganic particles. As the water-soluble polymer, the water-soluble polymers used in the water permeability adjusting membrane described above can be suitably used.
[0106] When the separator contains a water-soluble polymer, the content of the water-soluble polymer is preferably 0.1% by mass or more in 100% by mass of the separator in order to sufficiently disperse the inorganic particles and exert their effects, and is preferably 3% by mass or less in order to further suppress the water-soluble polymer from absorbing the electrolyte such as water and plasticizing the separator.
[0107] The separator may further contain other inorganic components such as conductive carbon and conductive ceramics. The content of other inorganic components in the separator is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 1% by mass or less, and particularly preferably 0.1% by mass or less, based on 100% by mass of the separator.
[0108] When the metal-air battery of the present invention has a separator, the average thickness of the separator is not particularly limited, but is preferably 1 μm to 1000 μm, more preferably 5 μm to 500 μm, and even more preferably 10 μm to 100 μm. The average thickness of the separator is the average value of measurements taken at random ten points using a micrometer.
[0109] The metal-air battery of the present invention preferably uses a separator made of an anion conductive membrane, but may also include a separator other than an anion conductive membrane. Examples of separators other than anion conductive membranes include nonwoven fabrics, filter paper, polyolefins such as polyethylene and polypropylene, polymers containing polytetrafluoroethylene moieties, polymers containing polyvinylidene fluoride moieties, cellulose, fibrillated cellulose, viscose rayon, cellulose acetate, hydroxyalkyl cellulose, carboxymethyl cellulose, polyvinyl alcohol-containing polymers, aromatic ring-containing polymers such as cellophane and polystyrene, halogen-containing polymers such as polyacrylonitrile moieties, polyacrylamide moieties, and polyvinyl fluoride moieties, polyamide moieties, polyimide moieties, and nylon. Examples of the polymer include ester moiety-containing polymers, poly(meth)acrylic acid moiety-containing polymers, poly(meth)acrylate moiety-containing polymers, hydroxyl group-containing polymers such as polyisoprenol and poly(meth)allyl alcohol, carbonate group-containing polymers such as polycarbonate, ester group-containing polymers such as polyester, carbamate or carbamide group-containing polymers such as polyurethane, agar, gel compounds, organic-inorganic hybrid (composite) compounds, ion exchange membrane polymers, cyclized polymers, sulfonate-containing polymers, quaternary ammonium salt-containing polymers, quaternary phosphonium salt polymers, cyclic hydrocarbon group-containing polymers, ether group-containing polymers, and inorganic materials such as ceramics.
[0110] Examples of the metal-air battery of the present invention include a zinc-air battery, a cadmium-air battery, a lithium-air battery, a sodium-air battery, a magnesium-air battery, a lead-air battery, a zinc-air battery, and a tin-air battery. Of these, the zinc-air battery and the cadmium-air battery are preferred, and the zinc-air battery is more preferred. EXAMPLES
[0111] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "%" means "% by mass".
[0112] <Water permeability test> (1) The water-permeability adjusting membrane and nonwoven fabric (thickness: 160 μm) of each of the Examples and Comparative Examples were cut into a circular shape with a diameter of 18 mm. (2) The weight of the cut nonwoven fabric is measured and m 1 The result was (g). (3) A gasket 45, the cut-out water-permeability adjusting membrane 11, the cut-out nonwoven fabric 53, and a pressing plate 51 were placed and fixed in this order at the bottom of a cylindrical cell having an inner diameter of 16 mm as shown in FIG. (4) 3 g of 6.7MKOH aqueous solution was gently poured into the cylindrical cell from the top. (5) The cylindrical cell was left at 25°C and normal pressure for 1 hour. (6) The weight of the nonwoven fabric is measured again. 2 The result was (g). (7) The water permeability rate K (mg / mm 2 / hour) was determined. M=m 2 -m 1 (I) K = M / (8 * 8 * 3.14) x 1000 (II)
[0113] <Ionic conductivity measurement test> A cell formed in the following cell configuration was allowed to stand in a thermostatic chamber at 25°C for 30 minutes, and then AC impedance measurement was performed under the following measurement conditions. The ionic conductivity was measured according to the following formula using the intercept component (Ra) obtained, the intercept component (Rb) when no measurement sample was inserted, and the film thickness obtained by the film thickness measurement method described in this specification. [Ionic conductivity (mS / cm)]=[Thickness of film (cm)] / [(Ra-Rb)×1000×1.77]
[0114] (Measurement conditions) Number of cells: 5 (average value) Cell configuration Working electrode: Ni plate Counter electrode: Ni plate Electrolyte: 6.7 mol / L potassium hydroxide aqueous solution saturated with zinc oxide Measurement sample: Permeability control membrane of each Example and Comparative Example, pretreated by immersing in the above electrolyte overnight Effective measurement area: 1.77cm 2 AC impedance measurement conditions Applied voltage: 10mV vs. open circuit voltage Frequency range: 100kHz~100Hz
[0115] <Discharge test> An air electrode was placed at the bottom of a cylindrical cell with an inner diameter of 25 mm, and an electrolyte (aqueous solution of 30 wt% potassium hydroxide), zinc powder, and a negative electrode current collector (Cu mesh) were placed on top of it. The discharge current was 100 mA, and the time that the discharge continued was measured and the time at which the inter-terminal voltage became 0 V was shown in Table 1 below.
[0116] Example 1 As a water permeability control membrane, the water permeability rate in the water permeability test was 0.1324 mg / mm 2 A polypropylene microporous membrane (thickness: 25 μm) was used for this water-permeability adjusting membrane. The results of a water permeability test and an ion conductivity measurement test are shown in Table 1 below. Ketjen black and polytetrafluoroethylene (PTFE) were mixed in a mass ratio of 9:1, kneaded, and then rolled to a thickness of 0.5 mm. The paste was pressed onto both sides of a Ni mesh to form an integrated catalyst layer (oxygen reduction layer). The catalyst layer and the water permeability control membrane were integrated by applying pressure using a flat plate press to prepare an air electrode. The results of a discharge test carried out using this air electrode (dischargeable time) are shown in Table 1 below and FIG.
[0117] Example 2 Magnesium hydroxide (average particle size: 250 nm) was used as inorganic particles, PTFE (average particle size: 300 nm, glass transition temperature: 115°C) was used as organic binder, and SBR (glass transition temperature: -1°C) was used as organic binder. The mixture was mixed in a volume ratio of 5:4:1 to form a slurry. The dispersion was then impregnated into a nonwoven fabric to prepare a water-permeability control membrane. The weight of the water-permeability control membrane [g / m 2 ] and the basis weight of the nonwoven fabric [g / m 2 The ratio of ] was 5:1. An air electrode was produced in the same manner as in Example 1, except that the obtained membrane was used as a water permeability adjusting membrane. The results of a water permeability test and an ion conductivity measurement test carried out on the water permeability adjusting membrane, as well as the results of a discharge test carried out using an air electrode (dischargeable time) are shown in Table 1 below.
[0118] Example 3 Magnesium hydroxide (average particle size 250 nm) and SBR (glass transition temperature -1°C) were mixed as inorganic particles in a volume ratio of 9:1 to form a slurry dispersion, which was then impregnated into a nonwoven fabric to prepare a water-permeability control membrane. 2 ] and the basis weight of the nonwoven fabric [g / m 2 The ratio of ] was 5:1. An air electrode was produced in the same manner as in Example 1, except that the obtained membrane was used as a water permeability adjusting membrane. The results of a water permeability test and an ion conductivity measurement test carried out on the water permeability adjusting membrane, and the results of a discharge test (dischargeable time) carried out using an air electrode are shown in Table 1 below and FIG. 3, respectively.
[0119] Example 4 An air electrode was produced in the same manner as in Example 1, except that two sheets of the membrane prepared in Example 2 were stacked and used as the water permeability adjusting membrane. The results of a water permeability test and an ion conductivity measurement test carried out on the water permeability adjusting membrane, as well as the results of a discharge test carried out using an air electrode (dischargeable time) are shown in Table 1 below.
[0120] Comparative Example 1 As a water permeability control membrane, the water permeability rate in the water permeability test was 0.2590 mg / mm 2An air electrode was produced in the same manner as in Example 1, except that a vinylon nonwoven fabric (thickness: 90 μm) was used. The results of a water permeability test and an ion conductivity measurement test carried out on the water permeability adjusting membrane, as well as the results of a discharge test carried out using an air electrode (dischargeable time) are shown in Table 1 below.
[0121] Comparative Example 2 An air electrode was produced in the same manner as in Example 1, except that a separator equivalent to that in the example described in Patent Document 3 was used as the water permeability adjusting membrane. The results of a water permeability test and an ion conductivity measurement test carried out on the water permeability adjusting membrane, as well as the results of a discharge test carried out using an air electrode (dischargeable time) are shown in Table 1 below.
[0122] [Table 1]
[0123] The results in Table 1 show that the metal-air battery comprising the air electrode of the present invention is capable of carrying out a discharge reaction for a long period of time. [Explanation of symbols]
[0124] 10: Air electrode 11: Water permeability adjustment membrane 13: Oxygen reduction catalyst layer 15: Breathable water-repellent film 20: Electrolyte 30: Atmosphere 41: Permeability measuring cell 43: Potassium hydroxide solution (6.7M, 3g) 45: Packing 51: Retaining plate 53: Nonwoven fabric (φ18, thickness 160 μm)
Claims
1. The water permeability rate measured by the following water permeability test is 0.01 mg / mm 2 / hour or more, 0.2mg / mm 2 1. An air electrode having a laminated structure including a water-permeability adjusting membrane having a water-permeability adjusting time of 1000 saturation ... Permeability test: (1) The water-permeability adjusting membrane and the nonwoven fabric (thickness: 160 μm) were each cut into a circular shape with a diameter of 18 mm. (2) Weigh the weight of the cut nonwoven fabric, m 1 Let it be (g). (3) The cut-out water permeability adjusting membrane is placed at the bottom of a cylindrical cell having an inner diameter of 16 mm, and the cut-out nonwoven fabric is further placed thereon. (4) 3 g of 6.7M KOH aqueous solution is gently poured into the top of the cylindrical cell. (5) The cylindrical cell is left at 25° C. and normal pressure for 1 hour. (6) Weigh the nonwoven fabric again, m 2 Let it be (g). (7) The water permeability K (mg / mm 2 / hour). M=m 2 -m 1 (I) K=M / (8*8*3.14)×1000 (II)
2. 2. The air electrode according to claim 1, wherein the water permeability adjusting film has an ionic conductivity of 20 mS / cm or more at 25°C.
3. 3. The air electrode according to claim 1, wherein the oxygen reduction catalyst comprises a carbon material.
4. 3. The air electrode according to claim 1, wherein the laminated structure further includes a water-repellent film having air permeability on the side of the catalyst layer opposite to the water-permeability adjusting film side.
5. A metal-air battery comprising the air electrode according to claim 1 or 2, a negative electrode, and an electrolyte solution.
6. 6. The metal-air battery according to claim 5, wherein the negative electrode is a zinc negative electrode.
Citation Information
Patent Citations
Mixture for air electrode
JP2016119289A
Metal air battery
JP2017174770A
Metal zinc battery
JP2017182996A